Experimental Study on Double Row Micropiles and Anchors Composite Retaining Structure in Deep Fill Site - Wenfeng Liu; Jie Mao; Hongxing Zhao; Guangbiao Shao (Advances in Civil Engineering)
In recent years, with the continuous advancement of urbanization in China and the gradual increase in the utilization scale of underground space, foundation pits may build in a narrow and compact environment. Meanwhile, miscellaneous fill layers in the city may cause construction difficulties when new foundation pits are excavated and supported. While we focus on the above problems, new retaining structure forms which are safe and economical are urgently needed. In this study, based on the excavation in a deep filling site in Jinan, the double row micropiles and anchors composite retaining structure is monitored under excavation, loading, and unloading conditions by installing sensors and testing. The stress and axial force distribution of the front and back row micropiles and anchors in the composite retaining system under different excavation depths and different loads are analyzed. The performance changes of the front and back row micropiles under different conditions and the contribution of anchors at different depths to the structure resistance during excavation and loading tests are discussed. The results show that double row steel piles and anchors composite retaining structure is feasible when excavating deep fill site in the urban area. In the composite retaining system, the stress of the front pile is greater than the back pile, the back pile has a lag when it starts working, and the axial force of the middle and upper anchor is greater than that of the bottom anchor.